Managing the dark side of digitalization in the future of work: A fuzzy TISM approach - Umesh Bamel; Satish Kumar; Weng Marc Lim; Nisha Bamel; Natanya Meyer (Journal of Innovation & Knowledge, 2022)
The rise of new-age technologies has spurred a new industrial revolution, resulting in a digital transformation in the way we work. The global COVID-19 pandemic has further accelerated the digitalization of work. While digitalization has many positive outcomes, its darker side should be proactively managed, not neglected. In this regard, this paper aims to identify and investigate human resource (HR) practices that can enable employees to manage the challenges caused by digitalization in the future of work (FoW). To do so, we employ fuzzy total interpretive structural modeling (TISM) on survey data acquired from senior professionals with HR responsibilities to ascertain the influence of HR practices in managing the dark side of digitalization in FoW. In doing so, we showcase the influence of (i) practices that promote work-life balance, (ii) democratization of work and work technologies, (iii) practices that promote employee empowerment, (iv) practices that promote entrepreneurial behavior, (v) reskilling for mastery, and (vi) practices that promote employee wellbeing in managing the dark side of digitalization in FoW, thereby advancing theory and practice of FoW.